Pengadaan Tanah Bagi Pembangunan Jalan Usaha Tani di Desa Adat Saren, Kecamatan Bebandem Kabupaten Karangasem - I Wayan Wahyu Dinata; I Made Suwitra; I Nyoman Sutama (Warmadewa Press, 2021)
Development is a human effort to manage resources to meet needs and improve the welfare of human life itself, as well as in the agricultural sector. Farmers really need the construction of a farm road in order to make it easier for farmers to get to the farm location comfortably and safely. The title of this study is Land Procurement for Agricultural Roads in The Village of Adat Soren District Bebandem Karangasem Regency This study aims to describe the process of land procurement at Soren Traditional Village which is carried out to promote the distribution of agricultural products, community transportation routes, river normalization and religious ceremonies. In addition, it will also review and identify problems that will be faced during the implementation of land procurement for the construction of agricultural commercial roads in Saren Indigenous Village, Bebandem Subdistrict, Karangasem Regency. The method used in this writing is an empirical research method that is equipped with legal methods as well as conceptual methods. The data sources used are primary data sources (interview results) as well as secondary data sources (reading materials from literature research. The results showed that the implementation of land procurement includes planning (determining road to the fields), preparation and implementation (socialization, review, approval, measurement and submission. The problem that arise in the implementation of agricultural land acquisition are based on several factors, including internal factors (including personal interests and development funds) and external factors (including geographical location and natural disasters